A high voltage bushing insulation layer material and preparation method thereof
By using the ethylene-phonyne closer to improve the tougard polypropylene and nano-composite fillers in the high-pressure suite insulation layer, it solves the problem of difficulty recycling and aging of the material, and realizes the recycling and aging resistance of the material.
Patent Information
- Application Number
- CN202410616523.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The existing high-voltage casing insulation layer materials are difficult to recycle and are prone to aging under the action of DC electric field, resulting in a decrease in service life.
The ethylene-ethylene-ethylene closette is used to increase the polypropylene, and the carbon nano-nano-gallery load of magnesium is preserved by multi-wall carbon nano-nano-controlled carbon nano-nano-balls, combined with the altosiloxyl oxygne substanide to modify it to form nano-composite filler point.
The recyclable and utilization of insulating materials is realized, and the aging performance of the material is significantly improved, and the service life of the cable is extended.
Smart Images

Figure CN118185188B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating materials, and specifically refers to a high-voltage bushing insulating layer material and a preparation method thereof. Background Art
[0002] The electric power industry is a basic industry related to the national economy and people's livelihood. With the continuous and rapid development of society and the continuous improvement of people's living standards, the demand for electricity is on the rise. The uneven distribution of energy bases and load centers has made the large-scale construction of low-loss long-distance power transmission networks increasingly important. High-voltage direct current transmission technology is a technology used for long-distance and large-capacity power transmission. The insulation safety and reliability of high-voltage direct current cables are closely related to the stability of the entire high-voltage direct current transmission network. Compared with AC cables, the development level of DC plastic cables is relatively backward. Since the electrical properties of polymer insulating materials under DC and AC are significantly different, under AC electric fields, the electric field distribution in the insulating medium is determined by the dielectric constant, which is not affected by temperature changes and electric field distribution. The electric field distribution in the insulating medium under the DC electric field mainly depends on the resistance, which is very sensitive to changes in temperature and electric field, and sometimes can differ by several orders of magnitude; the common high-voltage bushing insulation material is cross-linked polyethylene (XLPE), while traditional cross-linked polyethylene DC cable insulation has the disadvantages of many impurities, complex production process, and non-recyclability. Polypropylene has good chemical corrosion resistance and electrical insulation, and can be recycled to meet the requirements of green environmental protection and recyclability; under the long-term action of the DC electric field, the DC cable insulation material is prone to space charge accumulation, causing local electric field distortion and accelerating insulation aging, reducing service life. Therefore, the development of high-performance and environmentally friendly DC cable insulation is of great significance to the development of DC cable transmission technology.
[0003] The existing technologies currently have the following main problems: cross-linked polyethylene materials are difficult to recycle and the insulating materials are prone to serious aging. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-voltage bushing insulation layer material and a preparation method thereof. In order to solve the problem that cross-linked polyethylene materials are difficult to recycle, the present invention proposes a method of preparing recyclable insulation materials by toughening polypropylene with ethylene-octene copolymer, thereby realizing the recycling and reuse of cable insulation materials. Carbon nanospheres loaded with magnesium oxide are prepared by multi-walled carbon nanotubes and modified with vinyltrimethoxysilane as a composite filler, thereby achieving the technical effect of aging resistance of the insulation material.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: the present invention proposes a high-voltage bushing insulation layer material, which comprises the following components in parts by weight: 1-2 parts of nano-composite filler, 18-25 parts of ethylene-octene copolymer and 70-90 parts of polypropylene.
[0006] Preferably, the nanocomposite filler is prepared from the following components by weight: 7-9 parts of magnesium acetate, 35-45 parts of multi-walled carbon nanotubes, 175-225 parts of polymethyl methacrylate and 3.5-4.5 parts of vinyltrimethoxysilane.
[0007] Preferably, the method for preparing the nanocomposite filler specifically comprises the following steps:
[0008] S1, dispersing magnesium acetate, multi-walled carbon nanotubes and polymethyl methacrylate in 500 mL of deionized water, continuously stirring to obtain a mixed solution, and ultrasonically treating to obtain a reaction solution;
[0009] S2, spray drying the reaction solution obtained in S1 to obtain a precursor powder, and calcining in an argon atmosphere to obtain magnesium oxide carbon nanospheres;
[0010] S3, adding vinyltrimethoxysilane into 200 mL of anhydrous ethanol solution, adding the magnesium oxide carbon nanospheres obtained in S2, ultrasonically treating, filtering and drying to obtain a nanocomposite filler.
[0011] Preferably, in S1, the amount of magnesium acetate added to deionized water is 0.4-0.52 mg / mL; the amount of multi-walled carbon nanotubes added to deionized water is 2-2.58 mg / mL; the amount of polymethyl methacrylate added to deionized water is 10-12.86 mg / mL;
[0012] Preferably, in S1, the ultrasonic treatment power is 80-100w, and the time is 20-40min;
[0013] Preferably, in S2, the spray drying temperature is 180-220°C and the feed rate is 4-6 mL / min;
[0014] Preferably, in S2, the calcination temperature is 450-500°C and the calcination time is 2-3h;
[0015] Preferably, in S3, the amount of vinyltrimethoxysilane added to the anhydrous ethanol solution is 0.5-0.65 mg / mL;
[0016] Preferably, in S3, the ultrasonic treatment power is 60-80w and the time is 60-120min.
[0017] The present invention also provides a method for preparing a high-voltage bushing insulation layer material, which specifically comprises the following steps:
[0018] (1) adding ethylene-octene copolymer to a two-roll mixer, mixing at 120-140° C. for 3-5 min, adding nanocomposite filler to the ethylene-octene copolymer, and continuing mixing for 10-15 min to obtain a composite material;
[0019] (2) Add polypropylene to a double-roll mixer and mix at 180-200° C. for 3-5 min. Add the composite material obtained in step (1) to the polypropylene and continue mixing for 10-15 min to obtain a high-voltage bushing insulation layer material.
[0020] The beneficial effects achieved by the present invention are as follows: magnesium acetate is used as a magnesium source, polymethyl methacrylate is used as a pore-forming agent, and multi-walled carbon nanotubes are used as a supporting frame, and magnesium oxide carbon nanospheres are prepared by spray drying and high-temperature calcination, wherein the carbon nanotube walls have abundant interconnected pores and abundant dispersed magnesium oxide, and then vinyl trimethoxysilane is used for surface modification, and the carbon nanospheres are combined with the magnesium oxide carbon nanospheres by covalent bonds to obtain a nano-composite filler with good dispersibility, and polypropylene is used as a main body, and ethylene-octene copolymer and nano-composite filler are added and mixed to obtain a high-voltage bushing insulation layer material; the ethylene-octene copolymer can improve the mechanical toughness of polypropylene, and the nano-composite filler has good affinity with polypropylene, and can have The electrical properties of polypropylene composite materials are effectively improved; the nanocomposite filler with multi-walled carbon nanotubes as the supporting framework has good thermal conductivity. Carbon nanotubes are carbon crystals with strong hydrophobicity. Due to their unique structure, they have good stability and inhibit the aging of materials. Magnesium oxide is further loaded and surface modified to improve its dispersibility in insulating materials. As a deep well center, the mobility of carriers is reduced, thereby inhibiting the accumulation of space charges and improving the service life of cables. At the same time, the nanocomposite filler forms a cross-linked structure with polypropylene, which limits the dissociation of strong polar groups in the matrix and the ionization of impurity ions, thereby limiting the migration of conductive carriers and improving the insulation properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The results of thermal performance tests of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.
[0022] Figure 2 The results of the DC breakdown strength test of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.
[0023] Figure 3 The tensile strength results of Examples 1-3 and Comparative Example 1 of the present invention are shown in FIG.
[0024] Figure 4It is a result diagram of Examples 1-3 of the present invention and the elongation at break of polypropylene.
[0025] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0028] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0029] Ethylene-octene copolymer, brand: 8150;
[0030] Polypropylene, brand: F401;
[0031] Multi-walled carbon nanotubes (CasNo: 308068-56-6), Beijing Inokai Technology Co., Ltd., catalog number: A64678.
[0032] Example 1
[0033] A high-voltage bushing insulation layer material comprises the following components in parts by weight: 1 part of nano composite filler, 18 parts of ethylene-octene copolymer and 70 parts of polypropylene.
[0034] The nanocomposite filler is prepared from the following components by weight: 7 parts of magnesium acetate, 35 parts of multi-walled carbon nanotubes, 175 parts of polymethyl methacrylate and 3.5 parts of vinyl trimethoxy silane.
[0035] The preparation method of the nanocomposite filler specifically comprises the following steps:
[0036] S1, dispersing 0.2 g of magnesium acetate, 1 g of multi-walled carbon nanotubes and 5 g of polymethyl methacrylate in 500 mL of deionized water, stirring continuously to obtain a mixed solution, and ultrasonically treating at 80 W for 20 min to obtain a reaction solution;
[0037] S2, spray drying the reaction solution obtained in S1 at 180°C with a feed rate of 4 mL / min to obtain a precursor powder, and calcining at 450°C for 2 h in an argon atmosphere to obtain magnesium oxide carbon nanospheres;
[0038] S3, adding 0.1 g of vinyltrimethoxysilane into 200 mL of anhydrous ethanol solution, adding the magnesium oxide carbon nanospheres obtained in S2, ultrasonically treating at 60 W for 60 min, filtering and drying to obtain a nanocomposite filler.
[0039] The present invention also provides a method for preparing a high-voltage bushing insulation layer material, which specifically comprises the following steps:
[0040] (1) adding ethylene-octene copolymer to a two-roll mixer, mixing at 120° C. for 3 min, adding nanocomposite filler to the ethylene-octene copolymer, and continuing mixing for 10 min to obtain a composite material;
[0041] (2) Add polypropylene to a double-roll mixer and mix at 180° C. for 3 min. Add the composite material obtained in step (1) to the polypropylene and continue mixing for 10 min to obtain a high-voltage bushing insulation layer material.
[0042] Example 2
[0043] A high-voltage bushing insulation layer material comprises the following components in parts by weight: 1.5 parts of nano composite filler, 22 parts of ethylene-octene copolymer and 80 parts of polypropylene.
[0044] The nanocomposite filler is prepared from the following components by weight: 8 parts of magnesium acetate, 40 parts of multi-walled carbon nanotubes, 200 parts of polymethyl methacrylate and 4 parts of vinyltrimethoxysilane.
[0045] The preparation method of the nanocomposite filler specifically comprises the following steps:
[0046] S1, dispersing 0.23 g of magnesium acetate, 1.14 g of multi-walled carbon nanotubes and 5.71 g of polymethyl methacrylate in 500 mL of deionized water, stirring continuously to obtain a mixed solution, and ultrasonically treating at 90 W for 30 min to obtain a reaction solution;
[0047] S2, spray drying the reaction solution obtained in S1 at 200°C with a feed rate of 5 mL / min to obtain a precursor powder, and calcining it at 475°C in an argon atmosphere for 2.5 h to obtain magnesium oxide carbon nanospheres;
[0048] S3, adding 0.115 g of vinyltrimethoxysilane into 200 mL of anhydrous ethanol solution, adding the magnesium oxide carbon nanospheres obtained in S2, ultrasonically treating at 70 W for 100 min, filtering and drying, and obtaining a nanocomposite filler.
[0049] The present invention also provides a method for preparing a high-voltage bushing insulation layer material, which specifically comprises the following steps:
[0050] (1) adding ethylene-octene copolymer to a two-roll mixer, mixing at 130° C. for 3-5 min, adding nanocomposite filler to the ethylene-octene copolymer, and continuing mixing for 12 min to obtain a composite material;
[0051] (2) Add polypropylene to a double-roll mixer and mix at 190° C. for 4 min. Add the composite material obtained in step (1) to the polypropylene and continue mixing for 12 min to obtain a high-voltage bushing insulation layer material.
[0052] Example 3
[0053] A high-voltage bushing insulation layer material comprises the following components in parts by weight: 2 parts of nano composite filler, 25 parts of ethylene-octene copolymer and 90 parts of polypropylene.
[0054] The nanocomposite filler is prepared from the following components by weight: 9 parts of magnesium acetate, 45 parts of multi-walled carbon nanotubes, 225 parts of polymethyl methacrylate and 4.5 parts of vinyltrimethoxysilane.
[0055] The preparation method of the nanocomposite filler specifically comprises the following steps:
[0056] S1, dispersing 0.26 g of magnesium acetate, 1.29 g of multi-walled carbon nanotubes and 6.43 g of polymethyl methacrylate in 500 mL of deionized water, stirring continuously to obtain a mixed solution, and ultrasonically treating at 100 W for 40 min to obtain a reaction solution;
[0057] S2, spray drying the reaction solution obtained in S1 at 220°C with a feed rate of 6 mL / min to obtain a precursor powder, and calcining it at 500°C for 3 h in an argon atmosphere to obtain magnesium oxide carbon nanospheres;
[0058] S3, adding 0.13 g of vinyltrimethoxysilane into 200 mL of anhydrous ethanol solution, adding the magnesium oxide carbon nanospheres obtained in S2, ultrasonically treating at 80 W for 120 min, filtering and drying, and obtaining a nanocomposite filler.
[0059] The present invention also provides a method for preparing a high-voltage bushing insulation layer material, which specifically comprises the following steps:
[0060] (1) adding ethylene-octene copolymer to a two-roll mixer, mixing at 140° C. for 5 min, adding nanocomposite filler to the ethylene-octene copolymer, and continuing mixing for 15 min to obtain a composite material;
[0061] (2) Add polypropylene to a double-roll mixer and mix at 200° C. for 5 min. Add the composite material obtained in step (1) to the polypropylene and continue mixing for 15 min to obtain a high-voltage bushing insulation layer material.
[0062] Comparative Example 1
[0063] This comparative example provides an insulating layer material, which is different from Example 1 only in that the components do not contain nanocomposite fillers, and the other components and component contents are the same as those of Example 1.
[0064] Comparative Example 2
[0065] This comparative example provides an insulating layer material, which differs from Example 1 only in that the material does not contain multi-walled carbon nanotubes, and the other components and component contents are the same as those in Example 1.
[0066] Experimental example
[0067] 1. Thermal performance test:
[0068] DSC was used to analyze the thermal properties of the materials obtained in Examples 1-3 and Comparative Examples 1-2; 5 mg of the sample was placed in an aluminum crucible and heated from 20°C to 160°C at a rate of 10°C / min in a nitrogen environment. The crystallinity was calculated using the observed value of the melting enthalpy in the DSC curve. The initial crystallinity was before heating, and the aging crystallinity was after heating. The crystallinity reduction rate was calculated using the following formula:
[0069] Crystallinity reduction rate = (initial crystallinity - aging crystallinity) / initial crystallinity × 100%
[0070] Figure 1 This is a result diagram of the thermal performance test of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, after heat aging, the crystallinity reduction rates of Examples 1-3 and Comparative Examples 1-2 are 8.6%, 7.3%, 9.5%, 33.2%, and 16.7%, respectively; the crystallinity reduction rate of Examples 1-3 is significantly lower than that of Comparative Examples 1-2, indicating that the use of nano-composite fillers improves the aging resistance of the material. At the same time, the crystallinity reduction rate of Comparative Example 2 is significantly lower than that of Comparative Example 1, indicating that the use of multi-walled carbon nanotubes improves the aging resistance of the material.
[0071] 2. DC breakdown strength test:
[0072] Degassing of Example 1-3 and Comparative Example 1-2 in a vacuum oven at 80°C for 96h, and then aging at 115°C for 30d, to obtain thermally aged materials of Example 1-3 and Comparative Example 1-2; the DC breakdown strength of the materials obtained in Example 1-3 and Comparative Example 1-2 and the corresponding aged materials were measured at room temperature using a ball-plate electrode device; a sample with a thickness of 100 μm was immersed in transformer oil to avoid surface flashover, and a DC ramp voltage was applied at a rate of 500V / s until breakdown occurred. The breakdown voltage measured in Example 1-3 and Comparative Example 1-2 was the initial breakdown voltage, and the breakdown voltage measured in the thermally aged materials of Example 1-3 and Comparative Example 1-2 was the aged breakdown voltage, and the breakdown voltage reduction rate was calculated using the following formula:
[0073] Breakdown voltage reduction rate = (initial breakdown voltage - aging breakdown voltage) / initial breakdown voltage × 100%.
[0074] Figure 2 This is a result graph of the DC breakdown strength test of Examples 1-3 of the present invention and Comparative Examples 1-2. As shown in the figure, after heat aging, the breakdown voltage reduction rates of Examples 1-3 and Comparative Examples 1-2 are 16.9%, 16.5%, 17.3%, 42.6%, and 28.9%, respectively; the breakdown voltage reduction rate of Examples 1-3 is significantly lower than that of Comparative Examples 1-2, indicating that the use of nano-composite fillers improves the aging resistance of the material. At the same time, the breakdown voltage reduction rate of Comparative Example 2 is lower than that of Comparative Example 1, indicating that the use of multi-walled carbon nanotubes improves the aging resistance of the material.
[0075] After the multi-walled carbon nanotubes are modified, the dispersion performance of the nanocomposite filler in the polymer is better, and there is almost no agglomeration phenomenon. The small size effect of the particles can be fully utilized. They interact with the matrix in the form of heterogeneous nucleating agents. The end groups of the polymer molecular chains are connected to the surface of the particles, so that the molecular chains are arranged in an orderly manner, thereby improving the crystallinity of the material.
[0076] 3. Mechanical properties test
[0077] According to ASTM D638 standard, a universal material testing machine was used to test the stress-strain curves of Examples 1-3, Comparative Example 1 and polypropylene. The test temperature was 25° C., the tensile rate was 30 mm / min, and the specimens used in the experiment were 15 mm in length, 1.2 mm in thickness, and 4 mm in width. The tensile strength and elongation at break were calculated using the following formula:
[0078] Tensile strength = maximum load the specimen withstands during tension / original cross-section of the specimen.
[0079] Figure 3This is a result diagram of the tensile strength of Examples 1-3 of the present invention and Comparative Example 1. As shown in the figure, after heat aging, the tensile strengths of Examples 1-3 and Comparative Example 1 are 38.6 MPa, 38.9 MPa, 39.1 MPa, and 30.3 MPa, respectively; the tensile strengths of Examples 1-3 are significantly higher than those of Comparative Example 1, indicating that the use of nanocomposite fillers improves the tensile strength of the material.
[0080] Elongation at break = (length of the specimen at break - original length of the specimen) / original length of the specimen × 100%.
[0081] Figure 4 The result graph of the elongation at break of Examples 1-3 and polypropylene of the present invention is shown in the figure. As shown in the figure, after heat aging, the elongation at break of Examples 1-3 and polypropylene are 1156.5%, 1195.3%, 1166.9% and 632.1%, respectively; the elongation at break of Examples 1-3 is significantly higher than that of polypropylene, indicating that the addition of ethylene-octene copolymer and nano-composite filler improves the tensile properties of the material.
[0082] After adding the nanocomposite filler, the surface of the nanocomposite filler forms a mesh-like connection structure with the polymer molecular chain, which helps to increase the tensile strength of the material. At the same time, the addition of nanoparticles can induce heterogeneous nucleation, improve the crystallinity of the material, and increase the tensile strength of the material.
[0083] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0084] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A high voltage bushing insulation material, characterized in that: The invention comprises the following components in parts by weight: 1-2 parts of nano composite filler, 18-25 parts of ethylene-octene copolymer and 70-90 parts of polypropylene; The nanocomposite filler is a carbon nanosphere loaded with magnesium oxide and modified with vinyl trimethoxysilane, and is prepared from the following components by weight: 7-9 parts of magnesium acetate, 35-45 parts of multi-walled carbon nanotubes, 175-225 parts of polymethyl methacrylate, and 3.5-4.5 parts of vinyl trimethoxysilane; The preparation method of the nanocomposite filler specifically comprises the following steps: S1, dispersing magnesium acetate, multi-walled carbon nanotubes and polymethyl methacrylate in 500 mL of deionized water, continuously stirring to obtain a mixed solution, and ultrasonically treating to obtain a reaction solution; S2, spray drying the reaction solution obtained in S1 to obtain a precursor powder, and calcining in an argon atmosphere to obtain magnesium oxide carbon nanospheres; S3, adding vinyltrimethoxysilane into 200 mL of anhydrous ethanol solution, adding the magnesium oxide carbon nanospheres obtained in S2, ultrasonically treating, filtering and drying to obtain a nanocomposite filler.
2. A method for preparing the high voltage bushing insulation layer material according to claim 1, characterized in that: The specific steps include: (1) adding ethylene-octene copolymer to a two-roll mixer, mixing at 120-140° C. for 3-5 min, adding nanocomposite filler to the ethylene-octene copolymer, and continuing mixing for 10-15 min to obtain a composite material; (2) Add polypropylene to a double-roll mixer and mix at 180-200° C. for 3-5 min. Add the composite material obtained in step (1) to the polypropylene and continue mixing for 10-15 min to obtain a high-voltage bushing insulation layer material.
3. The method for preparing the high voltage bushing insulation layer material according to claim 2, characterized in that: In S1, the amount of magnesium acetate added to deionized water is 0.4-0.52 mg / mL; the amount of multi-walled carbon nanotubes added to deionized water is 2-2.58 mg / mL; and the amount of polymethyl methacrylate added to deionized water is 10-12.86 mg / mL.
4. The method for preparing the high voltage bushing insulation layer material according to claim 3, characterized in that: In S1, the ultrasonic treatment power is 80-100w, and the time is 20-40min.
5. The method for preparing the high voltage bushing insulation layer material according to claim 4, characterized in that: In S2, the spray drying temperature is 180-220°C, and the feed rate is 4-6 mL / min.
6. The method for preparing the high voltage bushing insulation layer material according to claim 5, characterized in that: In S2, the calcination temperature is 450-500°C, and the calcination time is 2-3h.
7. The method for preparing the high voltage bushing insulation layer material according to claim 6, characterized in that: In S3, the amount of vinyltrimethoxysilane added to the anhydrous ethanol solution is 0.5-0.65 mg / mL.
8. The method for preparing a high voltage bushing insulation layer material according to claim 7, characterized in that: In S3, the ultrasonic treatment power is 60-80w, and the time is 60-120min.
Citation Information
Patent Citations
Antistatic material, preparation method and applications of antistatic material
CN102585349A
Preparation method of magnesium oxide with high specific surface area
CN114031098A
Silicon carbide ceramic chip and preparation method thereof
CN115433018A